Effect of Bioslurry Concentration in Feed on The Growth and Survival of Milkfish (Chanos chanos Forsskal) - Zaenab, St; Masriah, Andi; Suryahman, Agus (Hasanuddin University, 2022)
Bioslurry is cow excreta waste processed anaerobically as a nutritional by-product of biogas production, which contains proteins, carbohydrates, fats and minerals. This study aims to determine the concentration of solid bioslurry in feed and the concentration of liquid bioslurry in feed containing solid bioslurry, which is optimal for increasing the growth and survival of milkfish. The results showed that the best feed with a concentration of 50% solid bioslurry resulted in a growth of 100.05 grams ± 6.98 and a survival rate of 96.67% ± 1.15. A significant growth increase in feed with a high bioslurry content indicates that bioslurry contains nutrients capable of increasing growth energy in milkfish. The growth of milkfish continues to increase along with the increasing concentration of bioslurry liquid waste added to the feed as a source of probiotics. Adding 50 ml of liquid bioslurry into 100 grams of feed resulted in the best growth of 165.33 grams ± 2.08. Liquid bioslurry contains probiotic microbial bioactivators and functions to increase growth.